(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Feature selection has predominant importance in various kinds of applications. However, it is still considered as a cumbersome process to identify the vital features among the available set for the problem taken for study. The researchers proposed wide variety of techniques over the period of time which concentrate on its own. Some of the existing familiar methods include Particle Swarm Optimisation (PSO), Genetic Algorithm (GA) and Simulated Annealing (SA). While some of the methods are existing, the emerging methods provide promising results compared with them. This article analyses such methods like LASSO, Boruta, Recursive Feature Elimination (RFE), Regularised Random Forest (RRF) and DALEX. The dataset of variant sizes is considered to assess the importance of feature selection out of the available features. The results are also discussed from the obtained features and the selected features with respect to the method chosen for study.